Antimicrobial resistance patterns of bacterial colonization in urine of patients with spinal cord lesion admitted at Thai Red Cross Rehabilitation Center - Sikanjananun, Sutunchalee; Panyasriwanit, Sirikwan; Kitisomprayoonkul, Wasuwat; Suankrata, Chusana; Tantisiriwat, Natthiya (Chulalongkorn Medical Journal, 2023)
Background: The emergence of extended spectrum beta-lactamase (ESBL)-producing Escherichia coli and Klebsiella pneumoniae at the stand-alone Rehabilitation Center of the Thai Red Cross Society has become a concern for treatment of patients with neurogenic bladder. Objective: To identify commonly observed bacterial colonization in urine of patients with spinal cord lesions. Methods: Medical records of all 135 patients with spinal cord lesions and who were admitted to the Thai Red Cross Rehabilitation Center were retrospectively reviewed for demographic data, type of neurogenic bladder and bladder management, and common bacterial colonization in urine specimens with antimicrobial susceptibility reports. Results: Of the 135 spinal cord lesion patients, 100 were male with the median age of 47 years old: 85% of them had neurogenic bladder, 39.8% detrusor overactivity (DO), 35% DO with detrusor sphincter dyssynergia, 24.3% detrusor underactivity, and 1% mixed type. Escherichia coli was the most frequent isolate followed by Klebsiella pneumoniae. Both E. coli and K. pneumoniae were multidrug-resistant (MDR) strains: 100% resistant to penicillin, fluoroquinolones (FQ), trimethoprim/ sulfamethoxazole (TMP-SMZ), and amoxicillin-clavulanic acid (AMC); 66.7% resistant to cephalosporin; 28.6% resistant to carbapenems; and, 28.6% resistant to aminoglycosides. Conclusion: MDR E.coli and K. pneumoniae were the most commonly observed bacterial colonizations in patients with spinal cord lesion who were admitted at our institute. E. coli isolates are highly resistant to almost all antimicrobials except aminoglycosides and carbapenems. K. pneumoniae isolates are highly resistant to all antimicrobials which were firstly found resistant to aminoglycosides and carbapenems in the 2015.